2016
DOI: 10.1111/pan.12894
|View full text |Cite
|
Sign up to set email alerts
|

Accidental awareness during anesthesia in children

Abstract: This educational review explores the current understanding of accidental awareness during general anesthesia (AAGA) in children. Estimates of incidence in children vary between 1 in 135 (determined by direct questioning) and 1 in 51,500 (determined from spontaneous reporting). The lessons from the 5th National Audit Project of the Royal College of Anaesthetists and the Association of Anaesthetists of Great Britain and Ireland show that the characteristics of spontaneous reports of AAGA are extremely variable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…In their 2014 meta-analysis, Shen et al [ 38 ] reported that the prophylactic administration of dexamethasone, ondansetron, or their combination in pediatric strabismus surgery can reduce PONV incidence. In a 2016 guideline, ondansetron combined with dexamethasone—but not dexmedetomidine alone—was recommended to increase the effectiveness of PONV prevention in children scheduled for strabismus surgery [ 39 ]. In a 2019 meta-analysis [ 36 ], compared with placebo use, premedication with clonidine (another α2 agonist) decreased PONV incidence by 17% in children undergoing strabismus surgery, which is in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In their 2014 meta-analysis, Shen et al [ 38 ] reported that the prophylactic administration of dexamethasone, ondansetron, or their combination in pediatric strabismus surgery can reduce PONV incidence. In a 2016 guideline, ondansetron combined with dexamethasone—but not dexmedetomidine alone—was recommended to increase the effectiveness of PONV prevention in children scheduled for strabismus surgery [ 39 ]. In a 2019 meta-analysis [ 36 ], compared with placebo use, premedication with clonidine (another α2 agonist) decreased PONV incidence by 17% in children undergoing strabismus surgery, which is in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our preference is to utilize NMBA during EP ablation procedures, as any patient movement can result in error by the cardiology team and/or breath holding might be requested by cardiologists during ablation. The risk of awareness has been estimated as 0.74% in children undergoing general anesthesia . In adults, an important risk factor remains the use of NMBA .…”
Section: Discussionmentioning
confidence: 99%
“…The risk of awareness has been estimated as 0.74% in children undergoing general anesthesia. 11 In adults, an important risk factor remains the use of NMBA. 12 We generally reserve TIVA-based approaches for those cases with PONV which has failed a strategy of a subhypnotic propofol infusion.…”
Section: Ta B L Ementioning
confidence: 99%
“…AAGA is defined as the recall of events or experiences that occurred during anesthesia and is a potentially devastating complication affecting between 0.1% and 2% of all patients undergoing GA ( 8 10 ). Over three-quarters of the cases of AAGA are caused by a period of awareness under GA of less than 5 min duration.…”
mentioning
confidence: 99%
“…However, long-term adverse effects affect 41% of people with this condition ( 11 ). Patient recollection of AAGA range widely from nondistressing audiological recall to extremely distressing recollection of agony and paralysis, often associated with the development of posttraumatic stress disorder-like symptoms ( 10 , 12 ). Multiple potential risk factors for AAGA have been identified by the recent NAP5 study, including the type of surgery (obstetric, cardiac, and pediatric), higher patient American Society of Anesthesiologists score, and obesity ( 13 ).…”
mentioning
confidence: 99%